2012
DOI: 10.1371/journal.pcbi.1002578
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Dynamics of a Bidirectional Neural Interface

Abstract: Progress in decoding neural signals has enabled the development of interfaces that translate cortical brain activities into commands for operating robotic arms and other devices. The electrical stimulation of sensory areas provides a means to create artificial sensory information about the state of a device. Taken together, neural activity recording and microstimulation techniques allow us to embed a portion of the central nervous system within a closed-loop system, whose behavior emerges from the combined dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Parallel development of components could also accelerate the ultimate realization of a device compact and powerful enough to be used as clinical tool able to transfer data between the brain and external devices wirelessly through an implanted interface (Azin et al, 2011; Fan et al, 2011; Borton et al, 2013; Angotzi et al, 2014). In this work, we also demonstrated that the modular architecture does not affect BMI performances, showing results comparable with the ones achieved in Vato et al (2012); this result suggests that BMI systems developed in other labs could also be re-implemented in a modular manner. To help the interested scientist in doing this, most of the material used in this project is freely available on Si-Code website : http://www.sicode.eu/results/software.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Parallel development of components could also accelerate the ultimate realization of a device compact and powerful enough to be used as clinical tool able to transfer data between the brain and external devices wirelessly through an implanted interface (Azin et al, 2011; Fan et al, 2011; Borton et al, 2013; Angotzi et al, 2014). In this work, we also demonstrated that the modular architecture does not affect BMI performances, showing results comparable with the ones achieved in Vato et al (2012); this result suggests that BMI systems developed in other labs could also be re-implemented in a modular manner. To help the interested scientist in doing this, most of the material used in this project is freely available on Si-Code website : http://www.sicode.eu/results/software.…”
Section: Discussionsupporting
confidence: 89%
“…We extended the Dynamic Neural Interface described in Szymanski et al (2011) and Vato et al (2012, 2014) with the inclusion of a neuromorphic decoder module. This system uses the neural signals collected from a rat's brain to control the movement of an external object by means of a sensory and motor interface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaching prosthetic hand to the target is important aspect in BMI application. Force should be set so that, the artificial hand moves towards the target according to the determined force field [23]. Here we considered the Gaussian force field that, this force was designed to drive the external machine toward an equilibrium state (Eq.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…As has been confirmed with behavioral experiments (Talwar et al, 2002; Fitzsimmons et al, 2007; London et al, 2008; Do et al, 2011, 2012; Semprini et al, 2012), MiSt has the potential to be used as sensory feedback for closed-loop brain-machine-interface (BMI) devices (Vato et al, 2012; Liao et al, 2013). However, the short- and long-term effects of such artificial input to the brain have not been fully described.…”
Section: Introductionmentioning
confidence: 82%